Neoproterozoic syn‐glacial carbonate precipitation and implications for a snowball Earth. Issue 2 (16th September 2021) - Hood, Ashleigh v. S.; Penman, Donald E.; Lechte, Maxwell A.; Wallace, Malcolm W.; Giddings, Jonathan A.; Planavsky, Noah J.
Abstract: The Neoproterozoic 'snowball Earth' hypothesis suggests that a runaway ice–albedo feedback led to two intense glaciations around 717–635 million years ago, and this global ice cover would have drastically impacted biogeochemical cycles. Testing the predictions of this hypothesis against the rock record is key to understanding Earth's surface evolution in the Neoproterozoic. A central tenet of the snowball Earth hypothesis is that extremely high atmospheric CO2 levels—supplied by volcanic degassing over millions of years—would be required to overcome a strong ice–albedo feedback and trigger deglaciation. This requires severely diminished continental weathering (and associated CO2 drawdown) during glaciation, and implies that carbonate minerals would not precipitate from syn‐glacial seawater due to a lack of alkalinity influxes into ice‐covered oceans. In this scenario, syn‐glacial seawater chemistry should instead be dominated by chemical exchange with the oceanic crust and volcanic systems, developing low pH and low Mg/Ca ratios. However, sedimentary rocks deposited during the Sturtian glaciation from the Adelaide Fold Belt—and contemporaneous successions globally—show evidence for syn‐sedimentary dolomite precipitation in glaciomarine environments. The dolomitic composition of these syn‐glacial sediments and post‐glacial 'cap carbonates' implies that carbonate precipitation and Mg cycling must have remained active during the 50 million‐year Sturtian glaciation. These syn‐glacial carbonates highlight a gap in our understanding of continental weathering—and therefore, the carbon cycle—during snowball Earth. In light of these observations, a Precambrian global biogeochemical model (PreCOSCIOUS) was modified to explore scenarios of syn‐glacial chemical weathering, ocean chemistry and Sturtian carbonate mineralogy. Modelling results suggest that a small degree of chemical weathering during glaciation would have been capable of maintaining high seawater Mg/Ca ratios and carbonate precipitation throughout the Sturtian glaciation. This is consistent with a severe ice age during the Sturtian, but challenges predictions of biogeochemical cycling during the endmember 'hard snowball' models. A small degree of continental weathering might also help explain the extreme duration of the Sturtian glaciation, which appears to have been the longest ice age in Earth history.